Emerging Role of Non-Coding RNAs in Senescence - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Hussen, Bashdar Mahmud; Baniahmad, Aria; Branicki, Wojciech; Taheri, Mohammad; Eghbali, Ahmad (Frontiers in Cell and Developmental Biology, 2022)
Senescence is defined as a gradual weakening of functional features of a living organism. Cellular senescence is a process that is principally aimed to remove undesirable cells by prompting tissue remodeling. This process is also regarded as a defense mechanism induced by cellular damage. In the course of oncogenesis, senescence can limit tumor progression. However, senescence participates in the pathoetiology of several disorders such as fibrotic disorders, vascular disorders, diabetes, renal disorders and sarcopenia. Recent studies have revealed contribution of different classes of non-coding RNAs in the cellular senescence. Long non-coding RNAs, microRNAs and circular RNAs are three classes of these transcripts whose contributions in this process have been more investigated. In the current review, we summarize the available literature on the impact of these transcripts in the cellular senescence.